1975
DOI: 10.1001/archpedi.1975.02120490011005
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Therapy in Children

Abstract: Glucocorticoids cause growth retardation in children. We have studied the effect of these hormones on serum somatomedin (Sm) levels in seven children with nephrosis. Intravenous administration of methylprednisolone sodium succinate, 2.2 mg/kg, causes a rapid fall in serum Sm activity. The activity remains suppressed during continuous therapy, but returns toward normal when medication is omitted during the course of alternate-day therapy. We conclude that one reason for growth retardation secondary to continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Wolthers et al [3]reported that administration of GH reversed the glucocorticoid induced protein catabolic effect detected in the present study, which is in accordance with other reports [1, 2, 4, 17]. A consistent finding in human studies is decreased IGF-I bioactivity in parallel with the protein catabolic effects of pharmacological doses of glucocorticoids [10, 12, 19, 20]. The exact nature of this decreased IGF-I bioactivity with unchanged/increased total IGF-I levels is unclarified.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Wolthers et al [3]reported that administration of GH reversed the glucocorticoid induced protein catabolic effect detected in the present study, which is in accordance with other reports [1, 2, 4, 17]. A consistent finding in human studies is decreased IGF-I bioactivity in parallel with the protein catabolic effects of pharmacological doses of glucocorticoids [10, 12, 19, 20]. The exact nature of this decreased IGF-I bioactivity with unchanged/increased total IGF-I levels is unclarified.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, serum total IGF-I concentrations are normal or even elevated after both short-term and more prolonged exposure to glucocorticoids [1, 2, 5, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]. Several studies have, however, shown reduced serum IGF bioactivity following glucocorticoid administration [10, 12, 19, 20]. This reduced bioactivity was not detectable when glucocorticoids were added to normal serum, which suggests the effect to depend on the generation of endogenous inhibitors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Normal levels of somatomedins have been described in patients with Cushing syndrome and those treated with GC [20]. However, such patients may have a reduction in the biological activity of somatomedin [20, 21]. The negative correlation between pretreatment IGF-1 levels and height velocity in response to treatment demonstrates the importance of anomalies of the GH-IGF-1 axis in understanding abnormal growth in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients receiving alternate day corticosteroid therapy, somatomedin levels were noted to be higher on the days off steroids (14). Additionally, prednisone administration in pediatric renal allograft recipients resulted in a fall in somatomedin activity that was related to an increase in an inhibitor of somatomedin (16).…”
mentioning
confidence: 98%
“…Earlier clinical studies have also alluded to the possibility that corticosteroid associated growth retardation could be due to decreased somatomedin activity (14)(15)(16). In patients receiving alternate day corticosteroid therapy, somatomedin levels were noted to be higher on the days off steroids (14).…”
mentioning
confidence: 99%